Тенденції розвитку педагогічної освіти у країнах Південного Кавказу (кінець ХХ – початок ХХІ ст.) - Федорчук, Ірина (Studies in Comparative Education, 2013)
У статті представлено тенденції розвитку педагогічної освіти у країнах Південного Кавказу наприкінці ХХ – на початку ХХІ століття. Автор аналізує різні аспекти системи підготовки педагогічних кадрів в умовах зростання ролі знань, глобалізації та інтеграції Азербайджану, Вірменії та Грузії в європейський освітній простір. Виявлено позитивні й негативні тенденцій, притаманні педагогічній освіті цих країн. В статье представлены тенденции развития педагогического образований в странах Южного Кавказа в конце ХХ – в начале ХХІ столетия. Автор анализирует разные аспекты системы подготовки педагогических кадров в условиях повышения роли знаний, глобализации и интеграции Азербайджана, Армении и Грузии в европейское образовательное пространство. Выявлено ряд позитивных и негативных тенденций присущих педагогическому образованию этих стран. Having gained the independence in 1991 following the collapse of the USSR the South Caucasus countries (Armenia, Azerbaijan and Georgia) found themselves in a challenging situation – the social and economic transition period which followed independence and the discrepancy between existing education and the needs of market economy caused the fall of education quality and its efficiency. The new realities of the transition towards democracy and market economy imposed new requirements and a new role for education in the context of knowledge society. They also challenged the whole concept of teacher training since a teacher plays a significant role in the development of intellectual potential of the country. In this article the tendencies of teacher education development in Armenia, Azerbaijan and Georgia are presented based on the in-depth analysis of each country national legislative framework in the sphere of education and literature review (international studies and reports, statistical data and policy documents relating to teacher education). By studying the key commonalities and differences that have developed in the sphere of teacher education over more than twenty years of independence, the following tendencies are distinguished: decentralization of higher education, integration to the European education area, content modernization, quality assurance, transition towards continuous professional development of teachers, cooperation with international organisations, insufficient use of ICT in studying process, deteriorating status of the teaching profession. The author associates the developments and innovations in teacher education in the South Caucasus countries with the search to respond to challenges that arose during the reform of the education systems in the context of European and global tendencies.